Role of adipose tissue in facial aging - Wollina U (Dove Medical Press, 2017)
Uwe Wollina,1 Reinhard Wetzker,2 Mohamed Badawy Abdel-Naser,3 Ilja L Kruglikov4 1Department of Dermatology and Allergology, Academic Teaching Hospital Dresden-Friedrichstadt, Dresden, 2Department of Anesthesiology and Intensive Care Medicine, and Center for Sepsis Control and Care, Jena University Hospital, Jena, Germany; 3Department of Dermatology and Venereology, Ain Shams University Hospital, Cairo, Egypt; 4Wellcomet GmbH, Karlsruhe, Germany Abstract: Age-dependent modification of the facial subcutaneous white adipose tissue (sWAT) connected with reduction of its volume, modification of collagen content and adhesion between dermal and adipose layers can significantly influence mechanical stability of the skin and cause the development of aging symptoms such as wrinkles. Typical aging appearance in facial skin is at least partly connected with special phenotypical features of facial preadipocytes and mature adipocytes. In this paper, we have discussed the possible roles of local inflammation, compartmental structure of facial sWAT and trans-differentiation processes such as beiging of white adipocytes and adipocyte-myofibroblast transition in facial skin aging. Keywords: facial aging, adipose tissue, preadipocytes, adipocytes, inflammation, beiging, adipocyte-myofibroblast transition